Pengaruh Pendapatan Perkapita, Indeks Pembangunan Manusia Dan Pertumbuhan Ekonomi Terhadap Jumlah Penduduk Di Kota Banjarmasin - Norsyahida Sari; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research aims to know and analyze how much income per capita, human developmentindex, and economic growth of the population in Banjarmasin city. The method used in thisresearch is the quantitative method, with variable income per capita, human development indexand economic growth of population in Banjarmasin, Data Time series secondary take 10 ( Ten)years with data analysis techniques using multiple linear regression, with the test ofassumptions The results showed that the revenue of the Percapita and Human DevelopmentIndex were partially influential on the population in Banjarmasin. Still, economic growth didnot have a partial effect on the number of inhabitants in Banjarmasin. The Percapita revenue,Human development index, and economic growth simultaneously influence the number ofinhabitants in Banjarmasin city. The variable that is the dominant influence on the number ofinhabitants in Banjarmasin city is the human development index.